HEMATOLOGICAL PROFILE OF HIV/AIDS PATIENTS AT UDAYANA UNIVERSITY HOSPITAL - Prabasari, Pande Visca Gayatri; Wiradewi Lestari, Anak Agung; Wande, I Nyoman; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana; Vol 13 No 1 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i01.P12, 2024)
Human Immunodeficiency Virus (HIV) is a virus that will enter the body and infect white blood cells (lymphocytes), causing human immunity to decrease. Acquired Immune Deficiency Syndrome (AIDS) is the final stage that will appear after the HIV virus attacks the immune system, causing a variety symptoms. One of the complications that can be found in HIV / AIDS is hematological abnormalities such as anemia, thrombocytopenia, leukopenia and lymphopenia which can disrupt the quality of life of people with HIV / AIDS. The aims of this study to determine the hematological profile of people with HIV / AIDS such as the prevalence of anemia, thrombocytopenia, leukopenia, and lymphopenia. This study used a descriptive method with a cross-sectional approach involving 31 people. Data collection used medical records data at Udayana University Hospital. The results obtained from 31 people diagnosed with HIV/AIDS showed the majority were male at 71%, in the age group of 18-39 years at 45,1%, and in stage IV at 83,9%. Most HIV/AIDS patients experience a decrease in hemoglobin levels by 64.5%, a decrease in lymphocyte percentages by 54.8%, a normal platelet counts of 96.8%, and a normal leukocyte counts of 71%. It can be concluded that the prevalence of anemia is 64,5%, lymphopenia is 54.8%, thrombocytopenia is 3,2%, and leukopenia is 16.1% in people with HIV / AIDS.